Quality Control Analysis To Reduce Product Defects With The Lean Six Sigma Method And Fault Tree Analysis - Muchammad Yusuf Muchsinin; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2022)
This research was conducted at UD. SI in order to control the quality of plastic rack products by applying the lean six sigma method and fault tree analysis. This method is often applied when a problem occurs because it is effective as a data processing method and analyzes a major failure and finds the cause of a defect in the production process in controlling product quality and improving quality in the company. This research uses Lean Six Sigma and Fault Tree Analysis methods. This data retrieval is done by using primary data and secondary data. Primary data was obtained through observation, interviews with employees and staff in the production department, while secondary data was obtained from the company when conducting research. From the results of the study that for perforated shelves, the error rate achieved can be seen in the pareto diagram where there are three types, namely perforated shelves, crinkled shelves and thin shelves where the causative factors of the product can be seen in the fault tree analysis method, namely humans and machines as well as recommendation for improvement by monitoring and checking as well as operators at the time of production as well as conducting strict product quality checks which are expected to minimize repeated repetitions.